2019
DOI: 10.1101/2019.12.13.875773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TGFβ superfamily signaling regulates the state of human stem cell pluripotency and competency to create telencephalic organoids

Abstract: Telencephalic organoids generated from human pluripotent stem cells (hPSCs) are emerging as an effective system to study the distinct features of the developing human brain and the underlying causes of many neurological disorders. While progress in organoid technology has been steadily advancing, many challenges remain including rampant batch-to-batch and cell lineto-cell line variability and irreproducibility. Here, we demonstrate that a major contributor to successful cortical organoid production is the mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…In the absence of Shh signaling, organoids predominantly exhibited cortical character including expression of the apical and basal radial glial progenitor marker PAX6, the intermediate progenitor marker TBR2 (EOMES), deep cortical plate markers including TBR1, CTIP2 (BCL11B), and BHLHB5 (BHLHE22), and superficial layer markers such as SATB2, and BRN2 (POU3F2) (Figs. 1b and 3, see also 17, 25 ). Shh pathway-stimulated organoids by contrast expressed canonical GE progenitor and migratory interneuron markers such as NKX2.1, DLX1, DLX2, and OLIG2.…”
Section: Resultsmentioning
confidence: 84%
“…In the absence of Shh signaling, organoids predominantly exhibited cortical character including expression of the apical and basal radial glial progenitor marker PAX6, the intermediate progenitor marker TBR2 (EOMES), deep cortical plate markers including TBR1, CTIP2 (BCL11B), and BHLHB5 (BHLHE22), and superficial layer markers such as SATB2, and BRN2 (POU3F2) (Figs. 1b and 3, see also 17, 25 ). Shh pathway-stimulated organoids by contrast expressed canonical GE progenitor and migratory interneuron markers such as NKX2.1, DLX1, DLX2, and OLIG2.…”
Section: Resultsmentioning
confidence: 84%
“…Without Shh signaling, organoids exhibited cortical characteristics including expression of the apical and basal radial glial progenitor marker PAX6, the intermediate progenitor marker TBR2 (EOMES), deep cortical plate markers including TBR1, CTIP2 (BCL11B), and BHLHB5 (BHLHE22), and superficial layer markers such as SATB2, and BRN2 (POU3F2) (Fig. 1b, see also 17,25 ). Shh pathway-stimulated organoids by contrast expressed canonical GE progenitor and migratory interneuron markers such as NKX2.1, DLX1, DLX2, and OLIG2.…”
Section: Excitatory and Inhibitory Neuron Integration Within Organoidsmentioning
confidence: 99%
“…Over time in culture, many neurons within GE organoids expressed GABAergic inhibitory neuron markers such as GAD65 (GAD2) and GABA along with a variety of interneuron subtype markers (Fig. 1b, see also 17,25 ).…”
Section: Excitatory and Inhibitory Neuron Integration Within Organoidsmentioning
confidence: 99%
“…Furthermore, the way in which hiPSC cells are cultured in the lab may have an important effect on their ability to generate reproducible organoid structures. Indeed, a recent study from Watanabe et al ( 118 ) revealed that commonly used feeder-free hiPSC culture conditions (compared to fibroblast-supported), reduced their ability to generate reproducible high-quality cortical organoids by altering their pluripotency state. The authors however showed that these defects could be alleviated through the use of TGFß superfamily agonists, which increase the quality of organoid differentiation toward different brain areas as well as reproducibility across cell lines.…”
Section: Future Technological Challengesmentioning
confidence: 99%